Role of Modern Technology in Enhancing Integration Among Dentistry, Radiology, Nursing, Pharmacy and Emergency medical Services - Waood Basher Khalaf Alshammari , Badr Ali Al Hushaesh , Ahmad Saleh Ahmad Al Marshad , Ammar Abdullah Fahad Al Ali,Sarah duhay aldawsari, Lamis Abdulrahman Alansari, Dr. Abdullah Saleh Alghamdi, Fahad Hasan Mohammed Dakam , Omar Funaysan Alanazi , Ali Abdullah Ali Alshehri , Fehaid Dhewaimi Murid Alanazi, Mohammad Ali Alanazi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
This research review paper investigates the utilization of modern technology to enhance integration among different healthcare disciplines, focusing on dentistry, radiology, nursing, pharmacy and emergency medical services (EMS) services. The integration of technology has the potential to streamline communication, improve efficiency, and enhance patient outcomes within the healthcare system.Methods: A comprehensive review of existing literature was conducted to explore the role of technology in promoting collaboration across various healthcare disciplines. Relevant studies, articles, and reports were analyzed to identify the benefits, challenges, and future implications of integrating technology in dentistry, radiology, nursing, and pharmacy services.Results: The findings highlight the numerous advantages of leveraging technology to facilitate integration among healthcare disciplines. These include improved communication and coordination among healthcare professionals, enhanced access to patient information, increased efficiency in healthcare delivery, and ultimately, better patient care outcomes. However, the implementation of technology-driven integration also presents challenges such as interoperability issues, data security concerns, and resistance to change among healthcare professionals.Discussion: The discussion section explores the implications of the research findings and considers potential strategies to overcome the challenges associated with technology-driven integration in healthcare. It underscores the importance of interdisciplinary collaboration, standardized protocols, and ongoing training to maximize the benefits of technology while mitigating its drawbacks. Additionally, the paper discusses the future directions of technological advancements in healthcare integration and emphasizes the need for continued research and innovation in this evolving field.